Interrelationships between water use efficiency and light use efficiency in four row crop canopies - Kukal, Meetpal S.; Irmak, Suat (Agrosystems, geosciences & environment, 2020)
Quantitative evidence of light use efficiency (LUE) controls on water use efficiency (WUE) is lacking, especially comparatively across row crops. Field research experiments (2016–2018) were set up for maize (Zea mays L.), soybean [Glycine max (L.) Merr.], sorghum [Sorghum bicolor (L.) Moench], and winter wheat (Triticum aestivum L.), under optimal growth conditions in dry sub‐humid conditions. Overall, LUE was able to explain 52% of variance in WUE, and were related as WUE = 1.73 LUE, although crop‐specific variation was observed. Highest sensitivity of WUE to changes in LUE was found in sorghum, followed by soybean, winter wheat, and maize. Evapotranspiration per unit light absorbed by crop canopy, which is a measure of canopy conductance (gc) ranged from a minimum of 0.45 kg H2O MJ−1 in sorghum to a maximum of 0.68 kg H2O MJ−1 in maize. Slopes of WUE vs. LUE relationship were limited by energy‐limited upper ceiling of latent heat of vaporization and characterized distribution of absorbed energy into latent heat of vaporization and sensible heat. Vapor pressure deficit (VPD) accounted for 41% of variability in the WUE vs. LUE relationship, and the relationship was subject to change with VPD conditions higher or lower than 0.85 kPa. Seasonal evolution of crop‐specific gc was modeled and communicated as a function of heat accumulation during the growing season. The research findings contribute to quantification of critical parameters that bridge water and light use efficiency, and better understanding of the resource use in C3 and C4 agricultural row crops.